PENGARUH MOTIVASI TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASIONAL SERTA PENGARUH KINERJA GURU TERHADAP KEPUASAN KERJA (Studi Kasus Pada Guru Madrasah Tsanawiyah Kecamatan Pamotan Kabupaten Rembang) - Ikha Pudiyanti, 1352020030; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the effect of motivation on the performance of teachers who moderated the organizational culture as well as the influence of teacher performance on job satisfaction. Total population set a number of 101 respondents. As independent variables namely motivation, moderation is variable while the dependent variable of organizational culture teacher performance and job satisfaction. The analysis includes the validity, reliability, normality test, heteroscedasticity, determination test, F test to test the hypothesis. Results of analysis using linear regression and two-stage least squares method, it is known that motivation variable significant positive effect on the performance of the teacher, organizational culture does not affect the performance of teachers. As for the results of the regression testing with moderation models indicate that organizational culture is not able to moderate the effect of motivation on teacher performance, while the performance of teachers give positive and significant impact on job satisfaction. Job satisfaction and motivation are directly related to the performance of teachers. Job satisfaction and motivation felt by teachers can degrade performance and also improve the performance of teachers. A teacher who is satisfied with the work that earned will be motivated to improve the performance so the impact on the overall improvement of the teacher.Keywords: Motivation, Organizational Culture, Teacher Performance and Job Satisfaction